Pengaruh Perbedaan Suhu Air terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) - Putri Clarita Sihombing; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
This research aims to determine how significant is the influence of temperature against the growth and survival of tilapia fish and to know a good temperature for the growth of tilapia fish. The methods used in these research was a Randomized Complete Design method (RCD) with three treatments and three replicates those are T1 (27oC), T2 (29oC) and the T3 (31oC). The results showed the highest growth found in T2 treatment with 5.1 cm added length and weight increase of 21.15 g, then followed the T2 treatment with 3.7 cm added length and weight increase of 17.27 (g) and lowest growth found in the T3 treatment with the length increase of 2.6 cm and 15.27 g weigh enhancement. The highest survival value for the maintenance of the refractory treatment was in the T1 treatment of 76.67%. Supporting water quality parameters obtained were pH ranging from 6.6 to 7.4 and DO ranging 4.0 to 5.2 mg/l. The normal range of temperature for the maintenance of the tilapia fish ranging between 25-28oC, but the best temperature for the growth of Tilapia fish is 27oC. The difference in temperature give a noticeable or significant influence towards the growth and survival of fish Tilapia.Keywords: Temperature, Tilapia, Growth, Survival.